Pessary for Prevention of Preterm Birth and Perinatal Mortality in Pregnancies with a Short Cervix: Systematic Review and Meta-Analysis of Randomized Controlled Trials - Henrique Graf Provinciatto; Edward Araujo Júnior; Gustavo Yano Callado; Alan Roberto Hatanaka; Roberto Angelo Fernandes Santos; Evelyn Traina; Gabriela Ubeda Santucci França; Luiza Graça Coutinho; Alan Lebrão de Amorim; Lucas Almeida das Chagas; Rosiane Mattar; Marcelo Santucci França (Diagnostics)
Objective: This systematic review and meta-analysis aimed to evaluate the efficacy of cervical pessaries in preventing perinatal mortality and extreme preterm birth in pregnancies characterized by a short cervix. Methods: The analysis included data from nine randomized controlled trials (RCTs), incorporating a total of 3813 participants. These studies compared the use of cervical pessaries against standard care or other interventions in preventing preterm births in women with a short cervix, defined as less than 30 mm. The eligibility criteria for the trials included studies on asymptomatic pregnant women with a short cervix. The primary outcomes analyzed were perinatal mortality and the incidence of preterm birth before 28 weeks of gestation. Results: The results showed an imprecise effect estimate for perinatal mortality (OR = 0.93; 95% CI: 0.54 to 1.62). Similarly, the risk reduction for preterm birth before 28 weeks was also non-significant (OR = 0.76; 95% CI: 0.49 to 1.15). Substantial heterogeneity was observed among the studies (I2 = 62%), suggesting variability in the study results, which could have been influenced by differences in the study design, population, and interventions. Conclusions: Although the results were statistically inconclusive and the estimates imprecise, the confidence intervals still span possible benefit and harm. Thus, while the current evidence does not support the routine use of cervical pessaries, it also does not indicate an increased risk of fetal or neonatal mortality.